2021
DOI: 10.2196/24727
|View full text |Cite
|
Sign up to set email alerts
|

Correlations Between Facial Expressivity and Apathy in Elderly People With Neurocognitive Disorders: Exploratory Study

Abstract: Background Neurocognitive disorders are often accompanied by behavioral symptoms such as anxiety, depression, and/or apathy. These symptoms can occur very early in the disease progression and are often difficult to detect and quantify in nonspecialized clinical settings. Objective We focus in this study on apathy, one of the most common and debilitating neuropsychiatric symptoms in neurocognitive disorders. Specifically, we investigated whether facial e… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 49 publications
2
5
0
Order By: Relevance
“…The lower levels of AU 26 (jaw drop) and AU 45 (blink) also increased the risk of apathy. A recent study also showed that apathetic individuals have reduced facial reactions and eye contact with their surroundings, which is in line with the core symptoms of apathy 22 . Consistent with the previous study, 12 apathy was correlated with MFCC 4, which corresponds to a lower voice spectral energy.…”
Section: Discussionsupporting
confidence: 86%
See 2 more Smart Citations
“…The lower levels of AU 26 (jaw drop) and AU 45 (blink) also increased the risk of apathy. A recent study also showed that apathetic individuals have reduced facial reactions and eye contact with their surroundings, which is in line with the core symptoms of apathy 22 . Consistent with the previous study, 12 apathy was correlated with MFCC 4, which corresponds to a lower voice spectral energy.…”
Section: Discussionsupporting
confidence: 86%
“…Possible because apathetic individuals have fewer spontaneous facial expressions 46 . The impact of depression on speech intensity varied across different populations 10,22 . These discrepancies might be related to cultural differences in emotional expression and presentation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Specifically, aging of the orofacial motor cortex, which involves involuntary facial expressions, can cause a decline in cognitive control for the lower part of the face [ 17 , 18 ]. While facial aging is natural and inevitable for most people, multiple studies have suggested there are several markers of facial expression and recognition in neuropathological changes including epilepsy [ 19 ], Parkinson’s disease [ 20 ], Alzheimer’s disease [ 21 ], and other neurocognitive disorders [ 22 ]. Despite this, identifying the quantitative characteristics of facial aging is still limited.…”
Section: Introductionmentioning
confidence: 99%
“…In this context, new technologies are offering novel opportunities to develop customizable and easy-to-use instruments allowing to quantify not only cognitive performance but also neuropsychiatric symptoms [18,31]. Specifically, there is evidence that new technologies and sensors such as eye-tracking [33], tablet applications [34], automated speech analysis [35], and automated video analysis [36,37] can provide relevant information to improve apathy assessment in ND. One of the most studied apathy proxies in ND is the global level of activity, assessed during long timeframes (e.g., one week) using actigraphy [38][39][40].…”
Section: Introductionmentioning
confidence: 99%